Impact of land resource misallocation on carbon emission efficiency: empirical evidence from 274 cities in China - Wen, Zhongqi; Lee, Woon-Seek; Woo, Sheen (Frontiers in Environmental Science, 2025)
IntroductionWith the acceleration of urbanization and the implementation of the “dual carbon” goals, the impact of Land Resource Misallocation (LRM) on Urban Carbon Emission Efficiency (UCEE) has attracted increasing attention.MethodsBased on panel data from 274 Chinese cities during the period 2010–2022, we constructed a LRM index and employed a two-way fixed-effects model to empirically analyze the relationship between LRM and UCEE.ResultsThe results revealed that LRM significantly hindered the improvement of carbon emissions efficiency in cities. The mechanism analysis indicates that this negative effect is primarily transmitted through the obstruction of Industrial Structure Upgrading (ISU) and Green Technological Innovation (GTI). Further, regional heterogeneity tests showed that the suppressive effect was more pronounced in the central and western regions, small- and medium-sized cities, and non-resource-based cities.DiscussionIn terms of policy implications, deepening market-oriented reforms of the land system, optimizing land use structures, reducing administrative intervention in land allocation, and simultaneously promoting industrial upgrading and GTI to enhance UCEE are recommended.